Evaluation of sunflower (Helianthus annuus L.) based cropping systems for enhanced productivity and efficiency: Evaluation of sunflower (Helianthus annuus L.) based cropping systems for enhanced productivity and efficiency - T SELVAKUMAR; L RAJENDRAN; R SASIKALA; P L VISWANATHAN (Journal of Oilseeds Research, 2020)
A field experiment was conducted to study the performance of sunflower in emerging cropping system during 2017-18. The experiment was laid out in split plot design. Cropping systems (Cotton-sunflower, Maize-sunflower, Soybean-sunflower and Sunflower-groundnut) were raised in main plots and fertilizer levels (RDF, STCR and 50% STCR) were implemented in subplots. Among the cropping systems, maize – sunflower cropping system gave the highest BCR (1.53) followed by sunflower-groundnut (1.49). Among the fertilizer levels, STCR based fertilizer application recorded significantly greater yield increase than RDF.